Functional Characterization of the Grapevine γ-Glutamyl Transferase/Transpeptidase (E.C. 2.3.2.2) Gene Family Reveals a Single Functional Gene Whose Encoded Protein Product Is Not Located in Either the Vacuole or Apoplast - Philips, Joshua G.; Dumin, Walftor; Winefield, Christopher (Frontiers in Plant Science, 2019)
Gamma-glutamyl transferases/transpeptidases (E.C. 2.3.2.2, GGTs) are involved in the catabolism of many compounds that are conjugated to glutathione (GSH), which have a variety of roles. GSH can act as storage and transport vehicle for reduced sulphur; it is involved in the detoxification of conjugated xenobiotics and also acts as a redox buffer by utilising its thiol residue to protect against reactive oxygen species, which accumulate in response to biotic and abiotic stress. Furthermore, many distinctive flavour and aroma compounds in Sauvignon blanc wines originate from odourless C5- and C6-GSH conjugates or their GGT catabolised derivatives. These precursors are then processed into their volatile forms by yeast during fermentation. In many plant species, two or more isoforms of GGTs exist that target GSH-conjugates in either the apoplast or the vacuole. A bioinformatics approach has identified a sole GGT in grapevine (Vitis Vinifera), VvGGT3, which is intriguing given the variety of roles of GSH and GGTs in plant cells. Functional characterisation of VvGGT3 from cv. Sauvignon blanc was then undertaken. The VvGGT3 transcript is present in roots, leaves, inflorescences, tendril and at equal abundance in the skin, pulp and seed fraction of mature grape berries and shows steady accumulation over the course of whole grape berry development. In addition, the VvGGT3 transcript in whole grape berries is upregulated upon Botrytis cinerea infection as well as mechanical damage to leaf tissue. VvGGT3-GFP fusion proteins transiently over-expressed in Nicotiana benthamiana leaves was used to study subcellular localisation. To confirm VvGGT3 activity and localisation in vivo, the fluorescent γ-glutamyl-7-amido-4-methylcoumarin substrate was added to N. benthamiana leaves transiently over-expressing VvGGT3. In combination, these results suggest that the functional VvGGT3 is associated with membrane-like structures. This is not consistent with its three closely related functionally characterised GGTs from Arabidopsis, radish and garlic.